Women caught in the conflict the culture war between traditinalism and feminism - Groothuis, Rebecca Merrill (Grand Rapids, MI Baker, 1994)
Includes bibliographical references and indexes.
Keywords: Women in Christianity; Feminism -- religious aspects -- Christianity; Evangelicalism